Balancing Traditional and Modern Methods in Sustainable HR Management: Menyeimbangkan Metode Tradisional dan Modern dalam Manajemen SDM yang Berkelanjutan - Saadia Haief Kadhum; Muayad Al-Saidi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Effective employee performance evaluation is crucial for sustainable human resource management (SHRM) in higher education institutions. Specific Background: The Middle Euphrates Technical University, spanning five Iraqi provinces, implements both traditional and modern evaluation methods, yet their impact on SHRM remains underexplored. Knowledge Gap: Limited studies have analyzed how these evaluation techniques influence the economic, social, and environmental dimensions of SHRM in the context of Iraqi higher education. Aims: This study aims to determine which evaluation methods more significantly affect human resource sustainability, focusing on the interplay between traditional and contemporary approaches. Results: Findings reveal that both methods are equally utilized by the university, with contemporary techniques slightly outperforming traditional ones in promoting sustainable HR practices. The economic dimension received the most institutional focus, while the social dimension showed greater progress than the environmental aspect in response to evaluation methods. Novelty: This research uniquely integrates organizational theory and HRM within the context of sustainability, highlighting the nuanced impact of evaluation methods on SHRM. Implications: The study underscores the need for higher education institutions to prioritize modern evaluation strategies that align with sustainability goals, fostering a balanced approach across economic, social, and environmental dimensions. Highlights: Modern methods slightly outperform traditional in HR sustainability. Economic dimension prioritized; social exceeds environmental progress. Sustainable HR evaluations boost institutional effectiveness. Keywords: Employee Performance Evaluation, Sustainable Human Resource Management, Traditional vs. Contemporary Methods, Higher Education, Middle Euphrates Technical University